Integrasi Mamangan Adat Minangkabau dalam Pembelajaran Bahasa Indonesia Berbasis Teori Konstruktivisme Sosial Vygotsky untuk Pengembangan Literasi Kritis - Mohd Bahaudin Ihsan; I Wayan Artika (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Critical literacy is an essential competence in Indonesian language education, enabling students to analyze, evaluate, and reflect on texts by considering their social, cultural, and ideological dimensions. This study aims to develop an Indonesian language learning model that integrates Minangkabau mamangan adat with Vygotsky’s social constructivist theory to enhance students’ critical literacy. As a form of local wisdom rich in philosophical, moral, and socio-cultural values, mamangan adat serves as an authentic and contextual learning medium that connects language, culture, and power relations. This theoretical study employs a qualitative approach using a systematic literature review of 72 sources published between 2019 and 2024, covering social constructivism, ethnopedagogy, critical literacy, and Minangkabau local wisdom. The analysis, conducted through narrative synthesis, reveals that mamangan adat aligns closely with key principles of Vygotskian theory, particularly cultural mediation, the zone of proximal development, and social scaffolding. The integration of mamangan adat facilitates critical literacy development through symbolic meaning deconstruction, cultural value analysis, and critical reflection on social power relations. The proposed framework emphasizes dialogic learning and positions students as active constructors of knowledge within culturally responsive pedagogy.